CNC Tool Path in Terms of Parametric Surface - Verma, Amit Kumar (My University, 2012)
Freeform surfaces, also called sculptured surfaces, have been widely used in various engineering applications. They are defined as surfaces containing one or more non-planar nonquadratic surfaces generally represented by parametric and/or tessellated models. Freeform surfaces, have been widely used in aerospace, automobile, consumer products and the die/mold industry. Freeform surfaces are usually designed to meet or improve an aesthetic and/or functional requirement. Sculptured surfaces are widely used in the design of complex products with aerodynamic features. These freeform surfaces are often produced by 3-axis Computer Numerical Control (CNC) machine tools using ball-end milling cutters. The utilization of CNC machines to manufacture complex surfaces has driven extensive research work, especially in the area of tool path generation. Various methodologies and computer tools have been developed in the past to improve efficiency and quality of freeform surface machining. From the literature review, it is found that there are number of different algorithms given by various researchers on the accurate tool path planning of free-form surfaces. The present study discusses the efficient and accurate tool path planning algorithm for smooth free-form surfaces in terms of planar cubic B-spline surface given by Lartigue et al. [16]. The procedure begins with interpolation of tool path in terms of cubic B-spline curve, and then computation of maximum scallop height and pick feed such that the maximum scallop height along the scallop curve is within the prescribed tolerance. As a next step of the present work, verification of the algorithm is done by machining a part on a CNC machine tool.
M.E. (CAD/CAM and Robotics)
Keywords: Free Form Surfaces; CNC Machines; Parametric Surfaces